BALI NURAGA-LAMPUNG: IDENTITY CONFLICT BEHIND THE POLICY - Zulfa, Eva Achjani (Indonesian Journal of International Law, 2014)
Indonesia is a nation richly blessed in heritage and culture. Its population consisted of 656 ethnic groups that spread from one end in Sabang to Merauke at the other end, and occupying more than 30,000 islands. In the last few years, a number of conflicts in Indonesia had escalated significantly in their magnitude, whether seen from the area of occurrence, from the backgrounds that triggered them, or the impact and their victims. The Bali Nuraga case in Lampung was a chronicle about the conflict between the people of Balinese descent and the indigenous people from Lampung in Sido Mulyo, it was an interesting subject to analyze, considering that the Balinese were not newcomers to the region. It has been told that this conflict was not essentially about religion, instead it was a conflict triggered by the persistent efforts by the Balinese in Bali Nuraga village to hold onto their identity.This paper will discuss about the ethnic issue that occured in Lampung regarding the existence of Balinese in Lampung. This conflict between Lampung against Bali, as we have seen from the presentation above was not about the Balinese people with their Hindu faith against the people from Lampung who were mostly Muslims; however, it was packaged that way by some parties to intensify the conflict.